Peran Kualitas Produk dan Store Atmosphere Dalam Keputusan Pembelian Pada Kopi Kenangan Mekarsari Cimanggis, Depok - Indah Noviyanti; Dedy Syahyuni (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2026)
This study aims to analyze the influence of product quality and store atmosphere on consumer purchasing decisions at the Kenangan Coffee outlet in Mekarsari Cimanggis, Depok. The background of this study is the increasing competition in the modern coffee beverage industry, which requires businesses to offer high-quality products and a pleasant shopping experience. Data were collected via a questionnaire distributed to 98 respondents who were customers at the outlet. The results indicate that the variables of product quality and store atmosphere have a positive and significant influence, both partially and simultaneously, on purchasing decisions. Product quality significantly influences consumers’ perceived value and satisfaction, while the store atmosphere affects their comfort and emotional experience while in the store. Simultaneously, these two variables account for 72.9% of the variance in purchase decisions. It is evident that consistent product quality is crucial in the coffee business, and to attract consumers’ attention, a pleasant and comfortable store atmosphere is a key factor in driving consumer purchase decisions.